Fighting words : individuals, communities, and liberties of speech - Greenawalt, Kent, 1936-2023 (Princeton University Press, 1995)
Should ""hate speech"" be made a criminal offense, or does the First Amendment oblige Americans to permit the use of epithets directed against a person's race, religion, ethnic origin, gender, or sexual preference? Does a campus speech code enhance or degrade democratic values? When the American flag is burned in protest, what rights of free speech are involved? In a lucid and balanced analysis of contemporary court cases dealing with these problems, as well as those of obscenity and workplace harassment, acclaimed First Amendment scholar Kent Greenawalt now addresses a broad general audience.